Si-Dimas: Model Peningkatan Kesejahteraan Duafa Berbasis Masjid - Dian Luthvita Nadila; Yeyen Novita; Zulafa Maulania Agta Dhiyanda; Arna Asna Annisa (CV. ULIL ALBAB CORP, 2021)
This research is aimed at studying solutions to improve welfare based on mosques by optimizing infaq and alms funds in fostered villages. This research uses qualitative methods and uses case studies. The main technique in collecting data is observation and in-depth interviews. The results of the research obtained indicate that the optimization of infaq and alms funds is one way to improve the welfare of poor people in the target villages through the SI-DIMAS concept. With the principle of fair and sustainable, this concept is endeavored to provide prosperity for the poor. The implementation of this concept is supported by the existence of synergy between LP2M as a campus research institute, KSEI as one of the UKMs engaged in the economy, mosque administrators as infaq and alms administrators at the mosque and the poor as aid in making UMKM from infaq and alms funds with the covenant qardhul hasan. (Monitoring and Evaluating) to minimize the risk of loss due to both the income that can be distributed as an effort to improve the welfare of the people in the target villages.